RIGHT TO EDUCATION AS A HUMAN RIGHTS - CONSTITUTIONAL AND LEGAL OUTLOOK - Kumar, Anjay; Sonawane, Ajay; Kharat, Madhuri (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Education is a strong foundational democratic value of continuous universal significance. It is the best platform for acquiring the skills, techniques, information and respect for the duties. The magnitude of the importance of education in life is multi-fold. Education is like the right to life as it is the mother of realizing other human rights. In the 21st Century worldwide activities are running on the wheels of education. To live a dignified life, education leads the way. The Universal Declaration of Human Rights declares that "Education shall be free, at least in the elementary and fundamental stages. Elementary education shall be compulsory." "Parents have a prior right to choose the kind of education that shall be given to their children." The International Covenant on Economic, Social and Cultural Rights says "Primary education shall be compulsory and available free for all." The right to education has been recognized as a constitutionally protected fundamental right in India. In Unni Krishnan Case (1993), the Supreme Court declared that the ‘right to education’ is part of the right to life under Article 21 of the Constitution of India. In 2002 through the Eighty-Sixth Constitutional Amendment Act, Article 21-A was inserted. Article 21A ‘requires the state to provide free and compulsory education of all children between the ages of six and fourteen in such a manner as the state may determine’. In 2009, the Indian Parliament enacted the Right of Children to Free and Compulsory. Education Act [RTE Act]. The Act aims to provide “free and compulsory education to all children of the age of six to fourteen years. The International Human Rights Bill and Constitution of India tries its best to ensure availability, accessibility, acceptability, adaptability of the right to education. The Article seeks to highlight various provisions related to right to education in international law and domestic law along with judicial interpretation. The authors also try to highlight the features of the Right to education Act, 2009.